2020
DOI: 10.1097/md.0000000000018994
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term smoking cessation among smokers enrolled in a university smoking cessation program

Abstract: Many lifelong smokers establish smoking habits during young adulthood. A university can be an effective setting for early smoking cessation. We evaluated long-term predictors of smoking cessation among smokers in a university setting. We longitudinally followed a cohort of smokers enrolled in a university smoking cessation program in Seoul, South Korea. Sociodemographic factors, smoking-related variables, and changes in smoking habits were assessed during 6-week visit sessions and follow-up telepho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“… Tobacco abstinence rate Short-term abstinence: < 3 months after quitting day [ 16 ] Medium-term abstinence: > 3 months and < 12 months after quitting day Long-term abstinence: > 12 months after quitting day [ 17 ] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Tobacco abstinence rate Short-term abstinence: < 3 months after quitting day [ 16 ] Medium-term abstinence: > 3 months and < 12 months after quitting day Long-term abstinence: > 12 months after quitting day [ 17 ] …”
Section: Methodsmentioning
confidence: 99%
“…An I 2 value of > 50% will be considered an indication of substantial heterogeneity [ 23 ]. Contour enhanced funnel plot will be used to detect any publication bias if more than 10 studies are included in this analysis [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…These reported experiences of participants resonate with the works of Pratt et al . [23] and Joo et al [2]. They demonstrated that individuals trying to stop smoking most likely experience shame, judgemental and embarrassing situations as well as victim blaming, within their social network.…”
Section: Discussionmentioning
confidence: 98%
“…Nicotine is a very addictive substance and the active component in tobacco, hence, the smoking behavior or constant repeated use of tobacco. However, smoking cessation is any process of discontinuing the excessive use of tobacco products [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hardening indicators, such as quit attempts and quit plans, may have limitations for evaluating hardening because they cannot transform completely into successful cessation 36 37. However, they have been shown to predict future smoking cessation38 and have been used frequently as hardening indicators in numerous studies 9 14 15 22. For the quit ratio as a hardening indicator, it cannot be established when quitting occurred.…”
Section: Discussionmentioning
confidence: 99%